2010
DOI: 10.1111/j.1475-6811.2010.01334.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses to interpersonal conflict among young adults: Influence of family of origin

Abstract: This study aimed to examine the role of family environment upon responses to interpersonal conflict in young adulthood, and to determine whether response patterns differed between men and women. Behavioral, affective, and cardiovascular responses of 17 young adults from families rated extreme (EXT) on scales of cohesion and flexibility were compared with those of 21 young adults from balanced (BAL) families. Participants engaged in 2 role‐play conflicts, 1 with a male confederate and 1 with a female confederat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
(50 reference statements)
1
5
0
2
Order By: Relevance
“…A path analytic model of the relations between childhood adversity, contemporaneous hostile/aggressive behavior, and HR stress responses provided a good fit to the data, and suggested that negative family-of-origin relationships can exert a lasting effect on heart rate responses to stress into adulthood via a pathway of hostile verbal behavior during challenging interpersonal interactions. These results are partially supportive of findings by Larkin et al (2010), who similarly observed more negative verbal behavior during a stressful role-play task among young adults reared in negative family environments. However, their findings of elevated DBP reactivity in response to stress diverged from the current study which found no effects of hostile verbal behavior on DBP reactivity or recovery.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A path analytic model of the relations between childhood adversity, contemporaneous hostile/aggressive behavior, and HR stress responses provided a good fit to the data, and suggested that negative family-of-origin relationships can exert a lasting effect on heart rate responses to stress into adulthood via a pathway of hostile verbal behavior during challenging interpersonal interactions. These results are partially supportive of findings by Larkin et al (2010), who similarly observed more negative verbal behavior during a stressful role-play task among young adults reared in negative family environments. However, their findings of elevated DBP reactivity in response to stress diverged from the current study which found no effects of hostile verbal behavior on DBP reactivity or recovery.…”
Section: Discussionsupporting
confidence: 87%
“…Prior studies of negative family environments have observed an effect on measures of HR (Torres et al, 2003) or BP (Larkin et al, 2010) only, without significant findings on other indices of cardiovascular functioning. These nuanced patterns of stress responsivity highlight the importance of examining multiple physiological indices through which adverse childhood environments may influence health.…”
Section: Discussionmentioning
confidence: 85%
“…Mayseless e Scharf (2009) sublinham esta ideia, na medida em que ligações desajustadas (pautadas por um elevado controle, triangulação e desvalorização), parecem predizer menores níveis de coping adaptativo, como o evitamento, a fuga e a negação das necessidades de vinculação aos pais. Os adolescentes caracterizados por este tipo de relação com os pais tendem a revelar maiores níveis de ansiedade de controle e confl ito no processo de independên-cia emocional (Larkin, Frazer, & Wheat, 2011). Também Kruse e Walper (2008), observaram num estudo com 649 adolescentes e jovens adultos de diferentes confi gurações familiares, que jovens de famílias tradicionais com níveis signifi cativos de desajuste relacional na família, sentem-se mais controlados e inibidos, apresentam mais desordens emocionais, mais negação das necessidades e vinculação e tendem a recriar relações inseguras ambivalentes com os demais.…”
Section: A Individuação E a Confi Guração Familiar No Desenvolvimentounclassified
“…Todas as experiências familiares, sejam elas as presentes ou passadas, relacionam-se com a auto perceção do indivíduo na idade adulta (Parra, Oliva, & Reina, 2013) e, de acordo com diversos estudos, um ambiente familiar pautado por uma realidade abusiva e conflituosa compromete o desenvolvimento psicoafectivo (e.g., Galea, 2010;Larkin, Frazer, & Wheat, 2011;Saucier, Wilson, & Warka, 2007). Deste modo, importa realçar, que as condições subjacentes à dinâmica familiar, nos primeiros anos de vida, desempenham um papel fundamental na segurança emocional e física (Galea, 2010).…”
Section: Palavras-chaveunclassified